“You’re Not from New York City, You’re from Rotherham” - Beal, Joan C. (Journal of English Linguistics, 2009)
This paper investigates the use of local accent and dialect features in the performance of Arctic Monkeys, a very successful indie band from Sheffield in the north of England. Previous work on variation in the sung pronunciation of British pop musicians by Trudgill (1983) and Simpson (1999) is reviewed. A qualitative analysis of an Arctic Monkeys performance is carried out to determine the extent to which features of northern and/or more specifically Sheffield English are used by Arctic Monkeys. The results are then discussed within a language-ideological framework, where it is argued that Arctic Monkeys are using features of local accent and dialect to index values such as authenticity and independence from the corporate machine.